KAJIAN PENGARUH TINGGI DINDING ABUTMENT TIPE CANTILIVER TERHADAP STABILITAS ABUTMENT RENCANA JEMBATAN TELUK BINGKAI KECAMATAN KENOHAN - Wiwarta, Yudi (KURVA S JURNAL MAHASISWA, 2014)
Kenohan sub-district is located in the northern area of KutaiKartanegara Regency, and the topography of this district much cleaved by theriver so that water transport is the primary choice for local people. The maindifficulty is the condition of the water transport streams and creeks areinfluenced by tides and seasons, where the dry season several tributariesexperienced a reduction of discharge even some drought so it is not possible topass. One possible alternate is to build a land transport infrastructure, namelyroads and with many rivers and streams that pass in the district are theconsequences far Kenohan one requires many bridges. One bridge is located inDistrict Kenohan located in Teluk Bingkai, where the existing condition of thebridge is a bridge while former logging roads for forestry purposes.In this study, will be more focused on the calculation of the load acting onthe bridge based on RSNI T-02-2005 on Standards Imposition For Bridges,bridge type which is designed composite bridge with steel girder structure,classification of long-span bridge with a plan B is 20 meters and K.300 uniformconcrete quality or 300 kg/cm2, the selected abutment type is the type withvariations caltiliver wall 5 meters high and 6 meters.From the calculation results obtained greatest axial force acting on theabutment at 12166,11 KN largest and shear forces permit 6507,79 KN. Inaddition, the results of the calculation shows that the steeper abutmentabutment will affect the ability to withstand shear, so that the higher theabutment, the ability to withstand shear will be smaller, so contradictory withthe ability to withstand rolling abutment pretty good, especially on the x-axisdirection abutment.